Intervención del terapista respiratorio en paciente masculino de 60 años de edad con enfermedad pulmonar obstructiva crónica. - Soto Vera, Carlos Steven (2022)
The present review work was carried out with the purpose of making available basic and elementary aspects of chronic obstructive pulmonary disease (COPD) in the geriatric patient. Being one of the pulmonary pathological processes due to airflow limitation associated with an abnormal inflammatory response to noxious particles or gases, it does not differ much from other age groups. The importance for the family doctor will be to keep the disease stable and provide a better quality of life, taking into account during the follow-up in these patients the appearance of symptoms that show advanced stages of the disease and the impact of the disease on daily life. Above all, the degree of family and social support available to the patient should be investigated. Therefore, the management of stable COPD is aimed at the prevention of the disease, relief of symptoms, prevention and treatment of complications and exacerbations. It must always be remembered that advanced age is a factor associated with mortality and the appearance of complications, which forces us to be aware of a possible hospitalization of the control patient.